2023
DOI: 10.3390/plants12020292
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nanoparticles in Response of Plants to Abiotic Stress at Physiological, Biochemical, and Molecular Levels

Abstract: In recent years, the global agricultural system has been unfavorably impacted by adverse environmental changes. These changes in the climate, in turn, have altered the abiotic conditions of plants, affecting plant growth, physiology and production. Abiotic stress in plants is one of the main obstacles to global agricultural production and food security. Therefore, there is a need for the development of novel approaches to overcome these problems and achieve sustainability. Nanotechnology has emerged as one suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(20 citation statements)
references
References 197 publications
0
20
0
Order By: Relevance
“…Nanoparticles based on iron oxides, phosphates, and goethite have been used to reduce the harmful effects of toxic elements and for environmental remediation, as they are effective in immobilizing and sequestering contaminants like As and Cd through sorption processes [78][79][80]. The application of nanoparticles has been reviewed by Tariq et al [81] and Al-Khayri et al [82].…”
Section: Role Of Nanoparticles Under Abiotic Stress Conditionsmentioning
confidence: 99%
“…Nanoparticles based on iron oxides, phosphates, and goethite have been used to reduce the harmful effects of toxic elements and for environmental remediation, as they are effective in immobilizing and sequestering contaminants like As and Cd through sorption processes [78][79][80]. The application of nanoparticles has been reviewed by Tariq et al [81] and Al-Khayri et al [82].…”
Section: Role Of Nanoparticles Under Abiotic Stress Conditionsmentioning
confidence: 99%
“…NPs can be used in agriculture because of their capacity to cross cellular barriers. NPs have gained popularity as an innovative agricultural tool because of their high solubility, compact size, and effective plant absorption (Al‐Khayri et al, 2023b). These characteristics, including their ability to increase abiotic stress resistance, make NPs attractive for agricultural applications (Figure 3B) (Hayat et al, 2023).…”
Section: Application Of Nanoparticles For Crop Improvement Against Hm...mentioning
confidence: 99%
“…Mg activates enzymes which affect plant growth and vigour (Chakraborty and Bose, 2020). Sireesha and Dawson., (2022) [115] observed in their experiment that among (10,15,20) kg Mg ha -1 , Mg 20 kg ha -1 resulted maximum growth and growth attributing characters, that is 5% more plant height, 11.3% more nodules plant -1 , 9.2% more dry weight (g plant -1 ) 4.5% more crop growth rate. This result obtains may be because of adequate amount of magnesium increases photosynthetic efficiency and promote healthy growth (Al-Juthery et al, 2021) [9] .…”
Section: Nitrogen (N)mentioning
confidence: 99%
“…Groundnut yield is also increased by S through improved chlorophyll synthesis resulting in higher growth (Ariraman et al, 2020) [96] . The element sometime helps to withstand cold, root growth, and the photosynthesis process (Al-Khayri et al, 2023) [10] . Dileep et al, (2021) [34] found in their experiment that among (20,30,40) kg S ha -1 dose ,40 kg ha -1 S helps to obtained maximum plant height (59.31 cm), highest dry matter accumulation (56.73 gm), maximum number of nodules plant -1 (47.53), while maximum crop growth rate (13.82 g/m 2 /day) and relative growth rate (0.008 g/m 2 /day) obtained @ 30 kg ha -1 S. Bhadiyatar et al, (2022) [16] found in their experiment that S did not influences as much on height and plant population in groundnut crop.…”
Section: Sulphur (S)mentioning
confidence: 99%
See 1 more Smart Citation